Spreading-Induced Damage to Short-Span Bridges in Christchurch, New Zealand. Issue 1 (February 2014) - Cubrinovski, Misko; Winkley, Anna; Haskell, Jennifer; Palermo, Alessandro; Wotherspoon, Liam; Robinson, Kelly; Bradley, Brendon; Brabhaharan, Pathmanathan; Hughes, Matthew
This paper discusses the performance of road bridges during the 2010–2011 Canterbury earthquakes and focuses on the response of bridges in liquefying soils undergoing lateral spreading. A characteristic spreading-induced mechanism for short-span bridges with rigid superstructures is presented and explored using four well-documented case studies. A series of pseudo-static analyses are then used to investigate the observed response of the bridges and their pile foundations in particular. Deformations and damage to the piles are evaluated and correlated with the spreading displacements, and key factors controlling the pile response and the development of the spreading-induced damage mechanism are identified.